2023
DOI: 10.1186/s12870-023-04293-w
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the molecular basis for photosynthetic parameters in Bambara groundnut (Vigna subterranea L. Verdc) under drought stress

Abstract: Background Assessment of segregating populations for their ability to withstand drought stress conditions is one of the best approaches to develop breeding lines and drought tolerant varieties. Bambara groundnut (Vigna subterranea L. Verdc.) is a leguminous crop, capable of growing in low-input agricultural systems in semi-arid areas. An F4 bi-parental segregating population obtained from S19-3 × DodR was developed to evaluate the effect of drought stress on photosynthetic parameters and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In order to protect from water deficits and heat waves, different plants have adapted various response mechanisms. For instance, improving cellular water retention via osmotic adjustment [ 23 ], keeping drought resistance by sugar signaling and transporting [ 24 ], soluble protein accumulation [ 25 ], and improving photosynthetic [ 26 ] as well as antioxidant activity to defend against oxidative stress [ 27 ]. Meanwhile, studies on combining drought resistance in various plants have found that plants with higher ploidy levels showed better performance under stress [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to protect from water deficits and heat waves, different plants have adapted various response mechanisms. For instance, improving cellular water retention via osmotic adjustment [ 23 ], keeping drought resistance by sugar signaling and transporting [ 24 ], soluble protein accumulation [ 25 ], and improving photosynthetic [ 26 ] as well as antioxidant activity to defend against oxidative stress [ 27 ]. Meanwhile, studies on combining drought resistance in various plants have found that plants with higher ploidy levels showed better performance under stress [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%